Investigation of trees as natural protective barriers using simulated blast environment. (December 2021) - Gan, Edward Chern Jinn; Remennikov, Alex; Ritzel, David
Highlights: An Advanced Blast Simulator was used to generate an accurate blast environment. The blast load and tree distance from the target were varied. Wave diagrams were used to track the blast wave-tree-target interaction. Dynamic structural response of trees was captured with strain gauges and video. Trees were demonstrated to reduce blast loads on a target downstream. Abstract: Blast barriers are commonly used for protecting critical infrastructure from blast effects. While rigid blast walls are the most frequently used barrier type, they are often unattractive and obtrusive. It is therefore practical to consider the use of natural barriers. The applicability of trees as natural blast barriers has not been studied widely. Apart from several recent studies investigating the performance of hedges using small explosive charges and large-scale high-explosive forest blowdown studies from the 1950s-1960s, no other published results on the mechanical response of vegetation and its blast wave mitigation potential are found in the open literature. This paper presents the experimental results of the interaction of far-field blast waves with trees aimed to evaluate the potential of trees in protecting infrastructure targets from blast threats. Full-scale trees were exposed to simulated far-field blast loads generated in an Advanced Blast Simulator. The dynamic structural response of the Juniperus Spartan trees subjected to blast wave and their blast sheltering potential were investigated. This paper revealed the potential for trees in attenuating far-field blast waves and shelter target structures. A numerical model based on Computational Fluid Dynamics was developed in ANSYS FLUENT to reveal the blast mitigation mechanism of barriers against far-field blast loads. The model was also used to explain experimental observations.